Uterine CD56dim and CD16+ Cells in Refractory Antiphospholipid Antibody-Related Pregnancy Loss and Chromosomally Intact Abortuses: A Case-Control Study - Mostafa F Gomaa; Abdeiiatif G Elkhouly; Mohammad M Farghly; Laila A Farid; Nahla M Awad (Wolters Kluwer Medknow Publications, 2017)
Aim: To evaluate the role of uterine natural killer (uNK) CD56dim and CD16+ cells in patients with refractory antiphospholipid, antibody-mediated, recurrent, pregnancy loss. Settings and Design: A case-control study was conducted between 2012 and 2015 at a university hospital. Patients and Methods: A group of 118 women with a history of antiphospholipid antibody syndrome experiencing fetal loss in spite of low dose aspirin (LDA) and low molecular weight heparin (LMWH) treatment in the current pregnancy were included in this study. A group of 32 patients undergoing an elective termination of viable pregnancies before 20 weeks were taken as controls. Suction evacuation was performed to collect abortus specimens, and uterine wall curettage was performed to collect decidua specimens, which were then stained using monoclonal antibodies specific to CD56 and CD16. Statistics: Statistical analyses were performed using the Statistical Package for the Social Sciences version 18 software. Chi-square and Fisher exact tests were used for making comparison between the groups. Results: Abnormal fetal karyotype was found in nine (9/97) cases of the study group, which means that abnormal karyotype accounts for only 9.3% of the causes of failure of treatment. Abnormal karyotype was found in four cases of the control group. Only cases with normal karyotyping were subjected to decidual uNK cells analysis. We found that CD56dim and CD16+ were found in the decidua of 79 cases (79/97), which means that aberrant natural killer cells expression might account for 81.4% of the cases of refractory antiphospholipid antibody (APA)-mediated recurrent pregnancy loss. Conclusion: CD56dim and CD16+uNK cells might be correlated with refractory APA-mediated recurrent pregnancy loss.